Pengaruh Stres Kerja Dan Work-Life Balance Terhadap Kinerja Karyawan Pada Generasi Z Di Serpong Utara Kota Tangerang Selatan - Lala Fadhlika; Lidya Pricilla (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. This study aims to examine the effect of job stress and work–life balance on employee performance among Generation Z employees in North Serpong, South Tangerang City, both partially and simultaneously. This research employed a quantitative approach. The population of this study consisted of Generation Z employees. The sampling technique used was non-probability sampling with a purposive sampling method, and the sample size was determined using the Lemeshow formula, resulting in 100 respondents. The data analysis techniques included validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results showed that job stress has an effect on employee performance with the regression equation ( Y = 12.397 + 0.673X1 ), a correlation coefficient of 0.597, a coefficient of determination of 0.357 or 35.7%, and hypothesis testing indicating that the calculated t-value was greater than the t-table value (7.372 > 1.984). Work–life balance was found to have an effect on employee performance with the regression equation ( Y = 19.055 + 0.529X2 ), a correlation coefficient of 0.699, a coefficient of determination of 0.488 or 48.8%, and hypothesis testing showing that the calculated t-value was greater than the t-table value (9.669 > 1.984). Furthermore, job stress and work–life balance simultaneously have a significant effect on employee performance with the regression equation ( Y = 10.127 + 0.344X1 + 0.402X2 ), a correlation coefficient of 0.744, a coefficient of determination of 0.553 or 55.3%, and hypothesis testing indicating that the calculated F-value was greater than the F-table value (60.102 > 3.090). Therefore, it can be concluded that H₀ is rejected and H₁ is accepted, meaning that job stress and work–life balance significantly influence employee performance.